Required Joinder of Parties in Civil Procedure and Extension of Res Adjudikata Effect: Legal Consequences of Court’s Failure to Detect Lack of Necessary Party - Knežević, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The paper deals with specific problem regarding required joinder of parties in litigation, namely legal consequences of rendering the judgment despite the failure to join a necessary party, but with court’s failure to detect the issue, i.e. is the lacking necessary party bound by judgement? Dominant opinion, both in domestic and foreign representative legal theory and case law, decline res adjudikata effect, while some Serbian scholars accept it. Research based on constitutional and dogmatic scale shows that extension of res adjudikata effect could not be deemed as Serbian lex lata. The concept of required joinder of parties is based on protection of right to be heard of all necessary parties, so the contrary standpoint would diminish, or moreover infringe such basic human right. In addition, there is no legal ground for such extension of res adjudikata effect, bearing in mind provisions of Serbian Code of Civil Procesure. Lastly, if lacking necessary party would be bound by judgement, the very concept of required joinder of parties would be reduced ad absurdum.
Keywords: required joinder of parties, boundaries of res adjudikata effect, extension of res adjudikata effect, right to be heard